Hepatitis C virologic response in hepatitis B and C coinfected persons treated with directly acting antiviral agents: Results from ERCHIVES. (March 2020) - Butt, Adeel A.; Yan, Peng; Aslam, Samia; Sherman, Kenneth E.; Siraj, Dawd; Safdar, Nasia; Hameed, Bilal
Highlights: There are scant data regarding HCV virologic response to DAAs in HBV/HCV coinfected persons. HCV treatment response in those with spontaneously cleared HBV infection is unknown. We found that HBV/HCV-coinfected persons have higher overall SVR rates with newer DAA regimens. The virologic response is graded, with decreasing SVR rates with increasing degree of liver fibrosis. HBV/HCV coinfected persons should be routinely offered HCV treatment in the absence of any specific contraindications. Abstract: Background: There are scant data regarding hepatitis C (HCV) virologic response to directly acting antiviral agents (DAAs) in chronic hepatitis B (HBV) and HCV coinfected persons. HCV treatment response in those with spontaneously cleared HBV infection is unknown. Methods: All HCV infected persons treated with a DAA regimen in ERCHIVES were identified and categorized into HBV/HCV-coinfected (HBsAg, HBV DNA or both positive), HCV-monoinfected, and resolved HBV (isolated HBcAb+). SVR rates were determined and compared for all groups. Logistic regression model was used to determine factors associated with SVR. Results: Among 115 HCV/HBV-coinfected, 38, 570 HCV-monoinfected persons, and 13, 096 persons with resolved HBV, 31.6% of HCV/HBV-coinfected, 24.6% of HCV-monoinfected and 26.4% with resolved HBV had cirrhosis at baseline. SVR was achieved in 90.4% of HCV/HBV-coinfected, 83.4% of HCV-monoinfected and 84.5% of those with resolved HBV infection ( P = 0.04 HCV/HBV vs. HCV monoinfected). In a logistic regression model, those with HCV/HBV were more likely to achieve SVR compared with HCV monoinfected (OR 2.25, 95% CI 1.17, 4.31). For HCV/HBV coinfected, the SVR rates dropped numerically with increasing severity of liver fibrosis (P-value non-significant). Factors associated with a lower likelihood of attaining SVR included cirrhosis at baseline (OR 0.85, 95% CI 0.80, 0.92), diabetes (OR 0.93, 95% CI 0.87, 0.99) and higher pre-treatment HCV RNA (OR 0.86, 95% CI 0.84, 0.87). Conclusion: HBV/HCV-coinfected persons have higher overall SVR rates with newer DAA regimens. Though not statistically significant, the virologic response is graded, with decreasing SVR rates with increasing degree of liver fibrosis as determined by the FIB-4 scores.